Development of ecological teaching book supplements based on local wisdom - Alif Putra Lestari; Sri Murtini; Bambang Sigit Widodo (Universitas Negeri Malang, 2021)
Textbooks are one of the important elements in the learning process that support the achievement of learning objectives, including in ecology courses. Based on the results of the analysis of existing teaching materials, there is no material about local wisdom and teaching materials still contain old material. Meanwhile, in Indonesia there are many local wisdoms that function to protect the environment in the midst of increasingly massive environmental damage and destruction. The material instructor's explanation also knew that currently there was no local wisdom and it was needed, so this was aimed at developing ecology textbook supplements based on local wisdom. The research design is an R&D model development research, the research subjects are students who are programming ecology courses at the Surabaya State of University Geography Education undergraduate, the research was conducted in November-December 2019 using the experimental class and the control class. Data collection in this study used several techniques, namely in the form of questionnaires (validation questionnaires and student response questionnaires), and written tests (pre-test and post-test) for students. This study aims to produce an ecological textbook supplement based on local wisdom that is feasible and can improve learning outcomes. The textbook supplements produced can be applied in the field, and can again help to improve the quality of content and design.